Progression of Subclinical Pachychoroid Neovasculopathy to an Active Neovascularization in the Presence of Acquired Vitelliform Lesions - Manoj Soman; Sameer Iqbal; Jay U. Sheth; Padmanaban Meleth; Unnikrishnan Nair (Case Reports in Ophthalmological Medicine)
We describe a unique case of bilateral acquired vitelliform lesions in a 67-year-old-female with pachychoroid associated with subretinal fluid in the right eye (OD) and a nonexudative choroidal neovascular membrane (CNVM) in the left eye (OS). Multimodal imaging performed at baseline and over the ensuing two years showed an increase in the OS vitelliform lesions with a concurrent transformation of quiescent CNVM to an exudative form. Further studies are warranted to gain better insight into the etiopathogenesis of these vitelliform lesions in pachychoroid and their potential role in instigating CNVM activation.